KARAKTERISTIK FISIK, KIMIA DAN SENSORI COOKIES BERBAHAN DASAR TEPUNG KOMPOSIT UWI (Dioscorea alata), KORO GLINDING (Phaseolus lunatus) DAN TEPUNG TERIGU - Kurniawan, Junjung Agung; Anandito, R. Baskara Katri; Siswanti, Siswanti (Universitas Sebelas Maret (UNS), 2018)
Functional food is processed foods containing one or more food components having certain physiological functions beyond their basic functions, proven not harmful and beneficial to health. Sources of functional food are found in local food as yam and lima beans. Yam and lima beans has a high water content that is not durable, then made a handler that is used as composite flour. Along with the development of snack products such as pastries are increasingly varied, then necessary to develop new products to improve the quality of existing products both in terms of nutritional content and appearance. This research to determine the effect of composite versus formulation on physical, chemical and sensory characteristics of cookies. This research use Completely Randomized Design (CRD) with one factor, that is variations of composite flour with wheat flour (F1= 0:100; F2= 20:80; F3= 40:60; F4= 60:40; F5= 80:20) (%b/b). The results of this research indicate that there are significantly different results on physical characteristics (texture), chemistry (moisture content, ash content, carbohydrate content, coarse fiber, calories and antioxidant activity) and sensory (color, taste and overall). The best formulation is F2 with the compositions (20% composite flour, fine granulated sugar 30 g, margarine 30 g, butter 7 g, vanilli 0,2 g, egg whites 25 g, egg yolk 7 g, cream of tar-tar 0,4 g, skim milk 14 g, salt 0,8 g, baking soda 0,2 g)Fungsional Food, Yam, Lima Beans, Composite Flour, Cookies